Pengaruh Penerimaan Dana ZISWAF, ROE, dan GWM terhadap BOPO dengan Firm Size sebagai Variabel Moderasi Periode Tahun 2018.Q1 – Tahun 2023.Q3 - Herison, Muhammad Fadhil Izzaini; Izzaini, Muhammad Fadhil; Eka wahyu Hestya Budianto (Journal Of Islamic Ekonomic and Business, 2024)
With firm size serving as a moderation variable, the purpose of this study is to assess the effects of ZISWAF Fund Receipts, ROE, and Reserve Requirement on BOPO from 2018.Q1 to 2023.Q3. Using the purposive sampling technique, the research sample was made up of financial sector businesses that were listed on the Indonesia Stock Exchange throughout the relevant time, which included five Sharia banks across a five-year period. Using Eviews 12 software, panel data regression analysis and moderated regression analysis (MRA) were used to analyze the data. According to the study's findings, institutional ownership will significantly reduce the value of financial sector enterprises between 2018 and 2023. BOPO was significantly impacted by ZISWAF Fund Receipts and Return On Equity (ROE) in the same period. Firm Size, however, was only able to moderate ZISWAF Fund Receipts and ROE during this time; it was unable to mitigate the impact of BOPO on reserve requirements. It is advised that, in order to generate more representative results, more moderating variables be used in future research, and the sampling be expanded to include other business sectors.